Multifidelity topology design of a maritime survey operation with UUVs - Morey, Danielle F.; Plate, Randall S.; Wakayama, Cherry Y.; Zabinsky, Zelda B. (Frontiers in Marine Science, 2024)
Advances in autonomous systems, maritime communications, and sensing technologies lead to increasing applications of unmanned underwater vehicles (UUVs). In this paper, we study a maritime survey operation topology design problem with UUVs that traverse an ocean environment and collect data from prespecified sensors or locations. This maritime scenario is analyzed via several models and simulation for the purpose of topology design for mission planning. We use a multifidelity approach to examine the trade-offs between different potential topology configurations of assigning UUVs to data collection sensors or locations. We develop three low-fidelity models that make simplifying assumptions. These models provide insight into the design characteristics and allow for sensitivity analysis with low computational cost. They are used to down-select potential configuration designs for further evaluation using a high-fidelity simulation model. A high-fidelity simulation model removes many simplifying assumptions and predicts how a topology design would perform under more realistic conditions. It gathers detailed performance metrics at the expense of higher computational cost. Our study uses this multifidelity approach to demonstrate key trade-offs for topology design. The optimal design of UUVs depends on mission-specific goals.